Socio-formative profile of the supervisors, heterogeneity and social hierarchy in the Teaching area of CAPES - Massi, Luciana [UNESP]; Carvalho, Helena; Giordan, Marcelo (Investigacoes em Ensino de Ciencias (IENCI), 2020)
The education and action of the supervisor is a scarcely studied subject, but a theme increasingly discussed in light of reports of difficulties experienced during post-graduate studies. We understand that this role of supervisor cannot be isolated from the context of their research area. The Teaching area, created in 2010, reflects several thematic groupings and carries a controversy associated with the moment of its creation by joining research areas that were previously independent. Bourdieu's sociology of science allows us to study these themes and advance in their understanding. In this article, we contribute to the understanding of the configuration of the Teaching area, by investigating the socio-formative profile of approximately 530 supervisors, pointing to heterogeneities and social hierarchies among these agents. The data from this study were collected through an online questionnaire and were statistically treated by Multiple Correspondence Analysis. Our results show very different profiles regarding the cultural and economic capital of the supervisors, as well as the condition they had to graduate as researchers. We question the implication of these results for the area of CAPES that treats as a single supervisor group with such distinct profiles.
Perfil socioformativo dos orientadores, heterogeneidade e hierarquia social na área de ensino da CAPES
Keywords: Academic research supervisors; Bourdieu's sociology of science; Multiple correspondent analysis; Teaching area